What is known about adverse events in older medical hospital inpatients? A systematic review of the literature. - Long, S; Brown, K; Ames, D; Vincent, C (2013)
PURPOSE: Large international studies have shown that older hospital inpatients are at particular risk of adverse events. The purpose of this review was to synthesize data from studies designed to assess the scale and nature of this harm, with the ultimate aim of informing the development of new safety and quality measurement tools to facilitate improved hospital care for these vulnerable patients. DATA SOURCES STUDY SELECTION: and data extraction A systematic search using Ovid SP and other sources was carried out, rigorous inclusion and exclusion criteria were applied and quality assessment of included studies was conducted. Data were synthesized to give a picture of the incidence, types, causes, preventability and outcomes of adverse events in older medical inpatients. RESULTS OF DATA SYNTHESIS: Nine relevant studies were identified. A wide range of adverse event incidences were reported, from 5.29 to 6.2% in re-analyses of large adverse event studies, to 60% in studies in which the development of 'geriatric syndromes' (e.g. falls, delirium, incontinence) was also considered to be adverse events. Important causative factors other than age included clinical complexity, co-morbidity, illness severity, reduced functional ability and lower quality of care. Adverse events in older people lead to unnecessary interventions with resultant complications and increased length of stay. CONCLUSION: More work is needed to understand the complex nature of adverse events in older inpatients. We must tailor safety measurement and improvement strategies to address challenges presented by the complexity of the geriatric syndromes and the processes of care encountered by older inpatients.